Analysis of multi-infeed receiving AC system with incompletely segmented VSC-HVDC - You Zuo; Minxiao Han; Bing Liu; Tamara Egamnazarova (Global Energy Interconnection)
When multiple LCC-HVDC transmission lines are densely fed into a receiving AC system, voltage dips can easily propagate in the power system, resulting in multiple LCC commutation failures simultaneously. The VSC-HVDC can be used to divide the receiving system into several interconnected sub-partitions and improve the voltage support capability of the receiving system. Compared with asynchronous interconnection, which completely separates the receiving systems with VSC-HVDC, incomplete segmentation with an AC connection is a more pertinent segmenting method for multilayer complex regional power grids. To analyze the voltage support capability of the VSC in incomplete segmentation, a micro-incremental model of the VSC was established, the operating impedance of the VSC was calculated, and the voltage support function of the VSC was quantified. The effect of the fault on the system short-circuit capacity was analyzed, and a calculation method for the multi-infeed short-circuit ratio in an incompletely segmented scenario was obtained. A VSC-segmented model of a two-infeed DC system was built on the EMTDC/PSCAD simulation platform, and the validity of the micro-increment model and accuracy of the proposed conclusions were verified.